NaCl and Phaeomoniella chlamydospora affect differently starch and sucrose metabolism in grapevines - Oliveira, Helena (2018)
Vineyards production is often affected by diseases as esca and Petri disease and by excess of salt. Phaeomoniella chlamydospora is one of the pathogenic fungi associated to esca disease, but its interaction with the plant under excess of salt remains unknown. Under controlled in vitro conditions, Vitis vinifera L. plants were exposed to 0, 20 and 100 mM NaCl and inoculated with P. chlamydospora. Both inoculation and salt stress decreased the levels of chlorophylls, which was aggravated when both factors were combined. NaCl 100 mM and, mostly, inoculation, decreased maximum fluorescence (F m ), variable fluorescence (F v ) and F v /F m . The activity of a -amylase decreased in plants exposed to 100 mM or inoculated but no synergic effect of these factors was observed; the activity of sucrose synthase was inhibited only by inoculations, whereas invertase was stimulated at 20 mM, but decreased with inoculation. Data support that both excess of salt and fungi inoculation negatively affect photosynthesis and sucrose metabolism, and that they also decrease amylase activity, which may play an important role in the increased levels of starch found in inoculated plants.